(untitled) (Journal of Universal Science Research, 2023)
This article discusses the importance of lipids in food production and highlights their role in enhancing flavor, texture, and nutritional value. It emphasizes the significance of lipids in heat transfer, cooking medium, and food preservation. The article also explores the impact of lipids on satiety and nutrient absorption. Overall, it provides a comprehensive overview of the various functions of lipids in food production.